2021
DOI: 10.4103/ijem.ijem_120_21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adherence, patient perception, and knowledge to statin therapy – A cross-sectional study

Abstract: Background and Objective: Cardiovascular diseases and its risk factors, such as diabetes and hyperlipidemia, are common in Indian population. Statin utilization is high across the country and it is important to assess the adherence because it plays an important role in treatment outcome. Statin adherence is not studied well in India. This study aims at measuring the adherence, perception, and knowledge of individuals on statin therapy. Study Design: Cross-sectional obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…24 In addition, the patient's knowledge and perceptions about their statin therapy significantly determined the patient's adherence. 25 However, it is important to mention that the recent National Lipid Association (NLA) guidelines estimated that the complete statin therapy intolerance is less than 5%. 19 Moreover, studies showed that low adherence to statins might be the main reason for inadequate LDL control and higher cardiovascular events risk.…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, the patient's knowledge and perceptions about their statin therapy significantly determined the patient's adherence. 25 However, it is important to mention that the recent National Lipid Association (NLA) guidelines estimated that the complete statin therapy intolerance is less than 5%. 19 Moreover, studies showed that low adherence to statins might be the main reason for inadequate LDL control and higher cardiovascular events risk.…”
Section: Discussionmentioning
confidence: 99%
“…In this study higher proportions of females and those with a history of coronary heart disease and atorvastatin as monotherapy had better adherence to statins. 9 Long-term adherence to statin therapy is reported to decrease over time according to various studies done earlier. 10 Poor long-term adherence to statin therapy is not only associated with higher event rates but also increased hospitalisations which in turn put an additional strain on the health services and also increase the overall healthcare costs as compared with the good adherence to therapy over the first 2 years of use.…”
Section: Clinical Evidence Of Poor Adherence In Indiamentioning
confidence: 99%
“…Common reasons for declining or discontinuing LLT use include a fear of actual or perceived side effects. 9 Although side effects with LLT are uncommon, statins may cause muscle symptoms and increase the risk of type 2 diabetes, use of ezetimibe may cause gastrointestinal side effects and muscle symptoms, and antiproprotein convertase subtilisin/kexin type 9 (PCSK9) monoclonal antibodies (mAbs) may cause a local site reaction, influenza-like symptoms, and nasopharyngitis., 17 In an analysis of data from the Patient and Provider Assessment of Lipid Management (PALM) registry, among 5693 adults recommended for statin therapy, 1511 (26.5 %) were not on statin therapy, including 153 patients who declined statin treatment and 464 who discontinued treatment. 18 Among untreated patients, fear of side effects (36.8 % of patients) was the most common reason cited for declining statin treatment, whereas perceived side effects (55.0 % of patients) was the most frequent reason reported for statin discontinuation.…”
Section: Side Effects Attributed To Lipid Lowering Therapiesmentioning
confidence: 99%
“…[10][11][12][13] Thus far, little is known about the potential role of patient knowledge of treatment goals of lipid-lowering therapy in cardiovascular disease, urging a further exploration and a comparison of dyslipidemia to DM. [14][15][16] In patient-centered health care, there are several interacting factors that can influence this level of implementation. 17 Physicians are challenged to indicate, inform about, prescribe, and maintain optimal therapy, while patients need to understand and use the information to manage and adhere to it.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with DM, some evidence exists that better knowledge of disease management goals has been associated with better outcomes, including glycemic control 10–13 . Thus far, little is known about the potential role of patient knowledge of treatment goals of lipid‐lowering therapy in cardiovascular disease, urging a further exploration and a comparison of dyslipidemia to DM 14–16 …”
Section: Introductionmentioning
confidence: 99%